Multi-instrument observations of the Pajala fireball: Origin, characteristics, and atmospheric implications - Vierinen, Juha; Aslaksen, Torstein; Chau, Jorge Luis; Gritsevich, Maria; Gustavsson, Björn; Kastinen, Daniel; Kero, Johan; Kozlovsky, Alexandre; Kværna, Tormod; Midtskogen, Steinar; Näsholm, Sven Peter; Ulich, Thomas; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Meteor observations provide information about Solar System constituents and their influx onto Earth, their interaction processes in the atmosphere, as well as the neutral dynamics of the upper atmosphere. This study presents optical, radar, and infrasound measurements of a daytime fireball that occurred on 4 December 2020 at 13:30 UTC over Northeast Sweden. The fireball was recorded with two video cameras, allowing a trajectory determination to be made. The orbital parameters are compatible with the Northern Taurid meteor shower. The dynamic mass estimate based on the optical trajectory was found to be 0.6–1.7 kg, but this estimate can greatly vary from the true entry mass significantly due to the assumptions made. The meteor trail plasma was observed with an ionosonde as a sporadic E-like ionogram trace that lasted for 30 min. Infrasound emissions were detected at two sites, having propagation times consistent with a source location at an altitude of 80–90 km. Two VHF specular meteor radars observed a 6 minute long non-specular range spread trail echo as well as a faint head echo. Combined interferometric range-Doppler analysis of the meteor trail echoes at the two radars, allowed estimation of the mesospheric horizontal wind altitude profile, as well as tracking of the gradual deformation of the trail over time due to a prevailing neutral wind shear. This combined analysis indicates that the radar measurements of long-lived non-specular range-spread meteor trails produced by larger meteoroids can be used to measure the meteor radiant by observing the line traveled by the meteor. Furthermore, a multistatic meteor radar observation of these types of events can be used to estimate mesospheric neutral wind altitude profiles.